HOMOTOPY PERTURBATION METHOD FOR SOLVING PARTIAL DIFFERENTIAL EQUATIONS - PANDIARAJA, D.; RAJENDRAN*, L.; VEERAMUNI, M. (International Journal of Mathematical Archive, 2018)
In this paper, Homotopy perturbation method is applied to solve some partial differential equations. Examples of PDEs are presented and give some useful help to solution of PDEs.